RAGAM DIALEK GEOGRAFIS NAMA JENIS MAKANAN DAN MINUMAN TRADISIONAL DI KECAMATAN MAJALAYA, KABUPATEN BANDUNG - Toni Heryadi (Pusbindiklat - LIPI, 2014)
This research was conducted in Kecamatan Majalaya. Kecamatan Majalaya is chosen as locus of this re- search because of its uniquenesses. One of its uniquenesses is a diversity of communities that have experienced acculturation and language. The data examined in this study amounted to one hundred and seven vocabularies. The method used in this study is descriptive, i.e. a method that aims to create a portrait or depiction on data, at- tribute, and relationships of phenomena under study in a systematic, factual, and accurate way. Thus, the expected result is to establish the description of vocabulary in form of a portrait or disclosure as it is. The purpose of this study is to identify the development of the vocabularies in Bandung’s geographical dialect, that is the frontier of lulugu Sundanese (formal language) and Bandung Sundanese (informal language). The results showed that there was a wide difference between Majalaya northern dialect with South Majalaya in phonologic-morphophonemic, such as language symptoms of metathesis, protesis, epentesis, aperesis, syncope, and apocope. Beside that, there are morphological differences in repeated words (reduplication) and compound (compositum), while in semantical differences, there may be a completely different form, but the inherent meaning is still the same.